2009
DOI: 10.1111/j.1478-3231.2009.02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacterial DNA in neutrocytic and non‐neutrocytic cirrhotic ascites by means of a multiplex polymerase chain reaction

Abstract: Identification of ascitic bactDNA is an appropriate alternative to bacterial ascite culture for pathogen identification in patients at risk for SBP. Its prognostic relevance as a proposed marker of bacterial translocation for certain risk groups has to be further evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
52
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 41 publications
(65 reference statements)
8
52
1
4
Order By: Relevance
“…Our 16S PCR was able to detect bacterial DNA in 100% (17/17) of culture-positive samples, and HRMA was able to correctly identify the bacterial species identified by culture in 70.6% (12/17) of positive samples in our study. The rate of positivity for bacterial DNA, 19.8% (21/106), detected from ascitic fluid samples in our study is comparable with the rates in other reported studies (3,4,8,9,11,12,(19)(20)(21)29). The overall sensitivity for detecting the presence of eubacterial DNA in an ascitic fluid sample and the specificity for the 16S PCR were high, at 100% (17/17) and 91.5% (85/89), respectively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our 16S PCR was able to detect bacterial DNA in 100% (17/17) of culture-positive samples, and HRMA was able to correctly identify the bacterial species identified by culture in 70.6% (12/17) of positive samples in our study. The rate of positivity for bacterial DNA, 19.8% (21/106), detected from ascitic fluid samples in our study is comparable with the rates in other reported studies (3,4,8,9,11,12,(19)(20)(21)29). The overall sensitivity for detecting the presence of eubacterial DNA in an ascitic fluid sample and the specificity for the 16S PCR were high, at 100% (17/17) and 91.5% (85/89), respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Although the microbiological spectrum found in our patient samples generally follows patterns previously described in other studies (3), it is interesting that 83.3% (10/12) of samples with concordant culture and HRMA results were Gram-positive organisms while other reports have Gram-negative organisms identified as the most common isolates from ascites (3,21). This higher prevalence of nosocomial infections follows the recent trend and may be due to the higher rate of exposure of our patient population to hospital environment.…”
Section: Discussionmentioning
confidence: 53%
“…Molecular methods based on species-specific PCR or broad- range PCR for detecting the 16S rRNA gene followed by sequencing for species identification are being increasingly used for the etiological diagnosis of purulent infections, including SBP, septic arthritis, or CAPD-related peritonitis (4,7,8,12,18,19). These assays have been shown to improve the diagnostic efficiency of culture methods due to their higher sensitivities, especially with samples obtained from patients who have been exposed to antibiotics prior to specimen sampling.…”
mentioning
confidence: 99%
“…Application of culture-independent PCR-based methods for the detection of bacterial DNA (bactDNA) in ascites has been proposed as a suitable tool to improve pathogen identification in patients at risk for SBP (6) and has indicated that bactDNA derives in most cases from a single pathogen (7)(8)(9). However, recent studies using 16S rRNA-based fingerprinting analyses have shown that ascites may also be polymicrobial (10,11) and that the bacterial spectrum is broader than that previously reported in context with SBP (11).…”
mentioning
confidence: 99%